Model Pembiayaan Agribisnis Berbasis UMKM di Kabupaten Sinjai (Studi Kasus: KUB Anggrek Desa Aska) - Nurfadillah, Nurfadillah; Astaman, Putra; Wahyuni, Yuyun; Nurhaliza, Nurhaliza; Fatimah, Sri Putri; Nasbar, Nasbar; Putri, Harmin Adijaya (Jurnal Riset Multidisiplin Agrisosco, 2023)
Financing in agribusiness, especially in businesses related to making MSME-based banana frond handicrafts, is needed in managing their business. The choice of the right financing model will depend on the needs and conditions of MSMEs. This study aims to analyze and describe the financing model at the Anggrek KUB of Aska Village, South Sinjai District, Sinjai Regency. The sampling method used is purposive sampling method. The results showed that Anggrek KUB of Aska Village currently only uses a financing model from personal capital, the P3AP2KB Office of Sinjai Regency, the UMKM Cooperative and Manpower Office of Sinjai Regency, and the Industry Trade and Energy Mineral Resources Office of Sinjai Regency. Alternative models for financing the Aska Village Orchid KUB include crowdfunding, venture capital, Microfinance Institutions (MFIs), and grants and aid programs.